MANFAAT DARI PROGRAM MENTORING DI FAKULTAS KEPERAWATAN DAN ILMU KESEHATAN UNIVERSITAS PELITA HARAPAN [THE BENEFITS OF A MENTORING PROGRAM IN THE SCHOOL OF NURSING AT UNIVERSITAS PELITA HARAPAN] - Grace Solely Houghty; Yakobus Siswadi; Ian Rudy Mambu (Polyglot, 2019)
Mentoring is a relationship between someone who has more experience and someone who has less. The literature shows that a mentoring program can enhance the academic success and character development of an individual. A mentoring program started in the school of nursing at UPH in 2013-2014 and it was a new experience for the students. The purpose of this study is to describe the benefits of the mentoring program. The research design is a qualitative descriptive study. The number of participants in the study were 17 mentors and 34 mentees. Narrative qualitative data were analyzed using content analysis. The results of the mentors content analysis of the benefits of the program revealed three themes: joint learning, effective communication skills, and caring for others. The results of the narrative data analysis of the mentees produced three themes: mutual respect, kinship, and effective academic learning. Based on this research, it is hoped that the mentoring program can be further developed, especially in the areas of ongoing recruitment and training of mentors.BAHASA INDONESIA ABSTRAK: Mentoring adalah suatu hubungan antara seseorang yang lebih berpengalaman dengan seseorang yang kurang pengalamannya. Literatur menunjukkan bahwa program mentoring akan memberikan dukungan untuk kesuksesan akademik dan pengembangan karakter diri. Program mentoring mulai dilaksanakan pada semester genap 2013-2014 dan merupakan hal yang baru untuk mahasiswa. Perlu untuk mengetahui gambaran program mentoring dalam bentuk data naratif. Tujuan penelitian adalah untuk menggambarkan manfaat dari program mentoring. Desain penelitian adalah studi deskriptif kualitatif. Jumlah partisipan dalam penelitian adalah 17 mentor dan 34 mentee. Data kualitatif naratif dianalisis dengan menggunakan analisis isi. Hasil analisis data naratif dari mentor tentang manfaat program mentoring menghasilkan tiga tema yaitu belajar bersama, keterampilan komunikasi yang efektif, dan rasa peduli kepada orang lain. Hasil analisis data naratif dari mentee tentang manfaat program mentoring menghasilkan tiga tema yaitu saling menghormati, rasa kekeluargaan, dan pembelajaran akademik yang efektif. Diharapkan program mentoring dapat dikembangkan lebih baik lagi khususnya untuk program perekrutan dan pelatihan yang berkelanjutan bagi mentor.